2006
DOI: 10.1111/j.1468-1331.2006.01113.x
|View full text |Cite
|
Sign up to set email alerts
|

Dilation of Virchow‐Robin spaces in CADASIL

Abstract: To precise the severity of dilated Virchow-Robin spaces (VRS) in CADASIL patients and to determine their correlation with clinical presentation and other abnormalities on cerebral Magnetic Resonance Imaging (MRI). Dilated VRS were previously associated with aging, hypertension, dementia, epilepsy or migraine. We already reported increased frequency of enlarged VRS in CADASIL patients when compared with family members without the affected haplotype. We analysed clinical and MRI data from 50 CADASIL patients col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 12 publications
3
63
1
4
Order By: Relevance
“…A special MR imaging change of cribriform cavities in the BG was the feature of this group. An "état criblé" or "status cribrosum" has been previously proved to be multiple dVRS in pathologic studies 19 and has been reported only among cases of vascular Parkinsonism, 20 subcortical ischemic vascular dementia, 21,22 or CADASIL 23 but has not been reported in the general population, to our knowledge. The present data further emphasize that the accumulation of multiple dVRS is not rare and can occur in elderly people in the absence of severe disability or dementia.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A special MR imaging change of cribriform cavities in the BG was the feature of this group. An "état criblé" or "status cribrosum" has been previously proved to be multiple dVRS in pathologic studies 19 and has been reported only among cases of vascular Parkinsonism, 20 subcortical ischemic vascular dementia, 21,22 or CADASIL 23 but has not been reported in the general population, to our knowledge. The present data further emphasize that the accumulation of multiple dVRS is not rare and can occur in elderly people in the absence of severe disability or dementia.…”
Section: Discussionmentioning
confidence: 74%
“…23 This may suggest 1 or several potential causes of dVRS with aging. 15 In this study, a higher grade of dVRS in the BG was observed more frequently in men than in women.…”
Section: Discussionmentioning
confidence: 99%
“…1 Diffusely enlarged perivascular spaces have also been reported, which have been hypothesized to occur in the context of certain pathologic conditions, including chronic microvascular ischemia, Alzheimer dementia, cerebral amyloid angiopathy, CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy), and mucopolysaccharidoses. [4][5][6][7][8] Regarding the function of perivascular spaces, several theories have been proposed. They are thought to play a role in immunologic processes in the brain, to provide a drainage route for interstitial fluid, and to provide a mechanism for equalization of intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Gradually, diffuse myelin pallor and rarefaction of hemispheric white matter (sparing the U fibers), deep focal lesions, particularly in periventricular areas and centrum semiovale, and lacunar infarctions in the white matter, basal ganglia and pons add up 21,24 . Virchow-Robin spaces tend to become dilated, perhaps by changes related to age or the progression of degeneration of penetrating cerebral arteries 25 . Further changes were demonstrated by MR spectroscopy: metabolic reductions in the relationship between mean NAA/Cr, NAA/Cho and Cho/Cr become obvious, especially in anterior (VS. posterior) regions of the centrum semiovale 26 .…”
Section: Genetics and Pathogenesismentioning
confidence: 99%